Economic effect of non-renewable and renewable energy on South Korea's agri-food sector: an input-output analysis - Siburian, Putri Wahyuni; Soo, Lim Song (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
South Korea’s Green New Deal has sparked debate over the balance between economic growth and environmental sustainability. While promising in concept, prior studies reveal tensions between these goals. This study empirically examines the economic viability of renewable energy policies using the Bank of Korea’s input-output (I/O) table to analyze the agri-food sector. Results show that non-renewable energy investments remain more economically profitable: a 1 million KRW investment yields 22,607 KRW more in production, 7,898 KRW more in value-added, and 2,004 KRW more in wages compared to renewables. However, non-renewables expose the economy to greater risk, supply shortages of 1 million KRW in this sector result in 53,484 KRW more in production losses than renewables. Thus, while non-renewable energy offers short-term economic advantages, renewable energy provides greater resilience. Long-term sustainability and reduced vulnerability to supply disruptions underscore the importance of transitioning toward renewable energy in building a stable and future-ready economy.